PERANCANGAN SISTEM WEB FILTERING DENGAN METODE DNS FORWARDING PADA JARINGAN KOMPUTER BERBASIS MIKROTIK ROUTEROS - Randy Ikhsan Ramadhan; Siti Madinah Ladjamuddin (Pusat Riset dan Inovasi Nasional, 2022)
Internet services in the age of technology like today are certainly helpful in our daily lives. There are so many benefits that can be obtained from this Internet services, such as finding sources of information, sending various information, online communicating, etc. However, it is undeniable that Internet services has negative websites. One of solution to prevent network users from accessing these negative websites is by implementing web filtering system. Therefore, the purpose of this research is to design a network security system that is used as web filtering to minimize access to negative websites on the Internet. To achieve this, the author used DNS Forwarding method to design the prevention system on a computer network. DNS Forwarding is a useful method for filtering out websites that have negative content and also useful for forwarding those websites to other websites that healthier and safer. The design of this network security system is applied to a computer network based on MikroTik RouterOS that utilizes the MikroTik RB941-2nD-TC hAP-Lite as the main device. The results of the web filtering system design with the DNS Forwarding method are proven to be able to minimize the access to negative websites on the user's network system when accessing the Internet.